ETR 300 Pandora Box / Yean Laura Kunyir ... [et.al] - Kunyir, Yean Laura; Morsid, Shamimi; Ben, Patricia Minda; Haron, Naseeha Sakina; Nasir, Mohamad Khairul Fadhillah (2010)
Pandora Box is a karaoke and café establishment that aims to provide the best gathering and leisure spot and at the same time keeping it distinguishable and unique from other competitors in the market. The main selling point for Pandora Box is the concept that we provide karaoke and café at one place. This is because we want to attract many customers to our premises as well as promoting this new trend to everyone. Our management team consists of five managers which are General Manager, Administration Manager, Marketing Manager, Operation Manager and Financial Manager. For our business, we are targeting people from the age of 18 and above. We believe this because this is the age whereby most outgoing and do outing with friends and family. In the future, targeted increase of 5-8 percent that will know our business and be our loyal customer because we believe that services that we offer will make Pandora Box memorable to the customer.